Neighbourhood sustainability: State of the art, critical review and space-temporal analysis. (December 2020) - Grazieschi, Gianluca; Asdrubali, Francesco; Guattari, Claudia
Highlights: A space-temporal bibliometric analysis on neighbourhood sustainability is performed. A regional differentiation on specific aspects of sustainability was found. Neighbourhood sustainability is over time a dynamic concept. A dynamic approach should be considered by rating systems. Abstract: This paper introduces a review on sustainability-related concepts at a neighbourhood scale. 3909 abstracts of papers on "neighbourhood sustainability" published between the late eighties and February 2020 were downloaded from Scopus in order to perform a text mining analysis. The concept of neighbourhood sustainability is studied and discussed at both geographical and temporal level, employing clustering methods. Marked differences in the elaboration of neighbourhood sustainability-related concepts can be tracked at spatial level and linked to the different socioeconomic, cultural and climatic conditions of the considered geographic areas. A significant temporal evolution of the concept can be also tracked with a focus on specific aspects of the sustainability concept in different periods of time. The analysis can help in defining more rigorous evaluation categories and criteria for neighbourhoods sustainability rating systems: new criteria should be included and an international homogenization is recommended in the definition of a common scheme of macro-categories, as well as local versions of the tools. Finally, the adoption of a dynamic approach, that doesn't stop after the projects realization, is proposed for the evaluation of the sustainability at a neighbourhood scale.